APLIKASI INFORMASI SARANA DAN PRASARANA UMUM DI KOTA SEMARANG BERBASIS ANDROID (Information Technology and Telematics, 2013)
Semarang as a city that is growing, have various public facilities and infrastructures that are often used by the people. But because of the lack of information about the location public facilities and infrastructures was then the society can only be estimated that the layout and the distance.  Public facilities and infrastructures such as ATM, Hospital, gas stations, restaurants, and there are still many other places is sometimes difficult to be sought for the places where was spread out in several locations. Because of that needs to be made a mobile application   that can display maps and travel route or direction toward the location that in research by using GPS (Global Positioning System) ?  Applications that was built using platform, using the technology android LBS (Location-Based Service), that is connected with the Google MAP. Result of this application can display information about  A quick public facilities and infrastructures are chosen users, featuring photos. Users can add comment, add photos or menambhakan type of public facilities and infrastructures place and the other, where administrator can mengupadate or edit information through server admin that has been made. The implementation system can be conclused applications that information can be run on a platform android, must be connected to the internet and activate fasilatas navigator namely Coordinate. For the next development this application should be added features call that can immediately called the place chosen, and will be able to menyimpann picture map so that it can be used in offline without internet. Keywords :  Application information public facilities and infrastructures, Platform Android,City of Semarang.